(untitled) (Research, Society and Development, 2022)
The purpose of this study was to determine the occurrence and risk factors of goats seropositive for small ruminant lentiviruses (SRLV) and Toxoplasma gondii on farms in Zabelê, Paraíba, Brazil. Blood samples were collected at ten goat dairy farms, making a total of 333 adult goats. The agar gel immunodiffusion test was used to determine the presence of antibodies against SRLV, while the indirect immunofluorescence reaction was used to search for T. gondii antibodies, considered positive for titers of 64 and over. For each herd, a questionnaire was applied in order to evaluate the characteristics of the farm, herd and type of management. The frequency of animals reactive to SRLV was 22.2% ± 0.41% (74/333), with seropositive goats found at 80% (8/10) of the sampled farms. The investigation of T. gondii antibodies revealed a frequency of 3.0% ± 0.22% (10/333), with antibody titers ranging from 64 to 4096, distributed among 40% (4/10) of the farms. Co-infection was diagnosed in a goat with a T. gondii antibody titer of 4096. Multivariate analysis indicated that the daily practice of cleaning facilities reduces the risk of SRLV infection by 2.31 (P < 0.001, SD = 0.33). This study emphasizes the need to intensify actions aimed at improving health management practices in dairy goat herds in the municipality.